Enhancing Tourist Visitation Through Establishing Repatronage Behavior - Yulandari, Ariefah (Institute of Computer Science (IOCS), 2024)
This research uses Osman's (1993) theory, namely the idea of ​​repeat purchases in stores giving rise to the concept of Repatronage Behavior. Over time, this concept was gradually applied to various service industries. Against this background, this research aims to examine the influence of repatronage behavior which is influenced by service quality, consumption emotions, satisfaction and price fairness. The population is tourists who visit the city of Solo with sampling using a purposive sampling method of 100 samples while hypothesis testing uses multiple regression analysis. The results of this research prove that the variables of destination image, consumption emotions, satisfaction have a positive or significant effect on repatronage behavior, while the variables of service quality and price rationality do not have a positive and insignificant effect on repatronage behavior